Challenges and Solutions in the Russian Energy Sector (Innovation and Discovery in Russian Science and Engineering,, 2018)
The book provides a comprehensive overview of the most recent and advanced research findings on energy production and management in the important Ural industrial region of Russia. The authors consider economic problems of energy development, management systems for sustainable energy, and investment mechanisms for energy. Comprised of chapters on energy efficient technologies, environmental aspects of using energy, and personnel for the power industry, the volume is ideal for a range of scientists and engineers interested in innovative approaches to generation and distribution of energy. Sheds light on R&D strategies developed within the foremost Russian universities; Details specific cases of issues, problems, and solutions within the Russia energy sector; Features chapters on sustainable energy generation/distribution and smart-grid technology as well as traditional systems.